Is sell-side research more valuable in bad times? - LOH, Roger (Institutional Knowledge at Singapore Management University, 2018)
Because uncertainty is high in bad times, investors find it harder to assess firm prospects and, hence, should value analyst output more. However, higher uncertainty makes analysts’ tasks harder so it is unclear if analyst output is more valuable in bad times. We find that, in bad times, analyst revisions have a larger stock-price impact, earnings forecast errors per unit of uncertainty fall, reports are more frequent and longer, and the impact of analyst output increases more for harder-to-value firms. These results are consistent with analysts working harder and investors relying more on analysts in bad times.